ANALISIS FAKTOR PENUNJANG DAN PENGHAMBAT PENGEMBANGAN OBJEK WISATA (Studi Pada Objek Wisata Alam Bola Palelo, Kecamatan Mollo Tengah, Kabupaten Timor Tengah Selatan ) - Marlin Rosanti Mellu; Tobias Tokan Bunga; Juita L.D. Bessie (Journal of Management Small and Medium Enterprises (SMEs), 2018)
This research aims to analyze the factors that support and hinder the development of natural tourismattraction Bola Palelo Subdistrict Mollo Central, South Central Timor Regency. Sampling techniqueused was purposive sampling by taking 15 people key informant and use descriptive analysis method.Based on the research results then summed up the factors that support the development of a naturalBola Palelo include the attractiveness, accessibility and marketing. As for the factors that impede thedevelopment of Bola Palelo include some aspect, the infrastructure aspect, the aspect ofgovernance/infrastructure, aspects of the community that includes the environment and culture,institutional aspects, aspects management, entrepreneur as well as aspects of aspects of research anddevelopment. Based on the conclusions above, the advice given was the need to build Tourism Office ofcoordination with the Government District, the village and the landowner in order to get a permissionto develop Bola Palelo as well as with the attention of the Government to put forward the tourism sectorneeds to be focused on the development of the potential of natural tourist attractions so as to attractother sectors to engage with addressing the factors restricting the development of Bola Palelo with howto provide such as a hut/shelter, restrooms and vending lapak (food and crafts typical of the localcommunity) around the site of the natural attractions , coordinate with the Office of Public ServiceDepartement to improve the infrastructure of highway that crosses Bola Palelo, utilizing thegovernance/infrastructure (irrigation systems, electricity and energy sources as well as network, systemand transport lines terminal, communication systems and security or surveillance systems) that havebeen available when it is about to develop these natural attractions, increase public awareness of thebenefits of tourism by socialization directl, and to build a good coordination between Dispar with theGovernment District, the village government and land owners in order to get the permissionsmanagement as well as the acquisition of land from the owner of the land so that it can be developed byinvolving employers in provide relief funds as well as help manage Bola Palelo and work together withthe academia in terms of research in the natural tourism object location so that the development can goaccording to plan.Keywords: Complementary Factors, Factors Restricting and Natural Attractions